KORELASI EFEKTIVITAS ANTIOKSIDAN EKSTRAK BUNGA MAWAR (Rosa damascena MILL.) DAN LIMBAH AIR BUNGA MAWAR (Rose water) SEBAGAI POTENSI TABIR SURYA - Sakti Purwanto, Diyan; Weni , Dewi; Tanafasa, Diana; Weni Sari, Dewi; Nurkharimah, Vivin (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
Roses (Rosa damascena Mill) are a commodity with economic value that has the potential to be a source of natural antioxidants. Further research related to the active compounds found in rose flower extract and waste water that can potentially be used as sunscreen for human skin health in accordance with standards by showing appropriate tests. The process begins with extraction, phytochemical screening, TLC, determination of antioxidant levels, SPF values, and continues with the manufacture of sunscreen gel  with  physical gel testing. The results showed that the antioxidant content in rose flower extract was 47.82 ± 0.09 µg/ml, which is classified as very strong, while rose flower water waste had an antioxidant content of 58.78 ± 0.10*µg/ml, which is classified as strong. Meanwhile, rose flower extract has an SPF value of 34.64 ± 0.08, and rose flower waste has an SPF value of 36.84 ± 0.05, which falls into the ultra-protection category, meaning the highest level of protection and does not cause tanning. There is a correlation between antioxidants and SPF that can be used in making rose flower sunscreen gel preparations and has physical tests that comply with the requirements.